Controllability of Nonlinear Fractional Systems with Multiple State and Control Delays (Journal of Nonlinear Modeling and Analysis, 2025)
This study focuses on examining the controllability of nonlinearfractional differential systems in finite-dimensional spaces, considering multiple delays in both state and control. For linear systems, the necessary andsufficient conditions for relative controllability are established through the definition and application of the Gramian matrix. For nonlinear systems, controllability conditions are derived using Schauder’s fixed point theorem.